2016
DOI: 10.1111/jfb.12881
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasites ofBrama australisfrom southern Chile: a tool for stock discrimination?

Abstract: The metazoan parasites of 403 specimens of the southern ray's bream Brama australis from three localities in southern Chile (Lebu 36° 70' S; 73° 40' W, Calbuco 41° 50' S; 73° 08' W and Punta Arenas 53° 10' S; 70° 50' W) were recorded. More than 23 400 parasite specimens belonging to 12 taxa were registered. Metazoan parasites were dominated by the copepod Hatschekia conifera, constituting 97% of the total number of parasites; the larval cestode Hepatoxylon trichiuri was the second most important parasite (2·1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The research group from the UA, Chile, has dealt with different subjects concerning helminths parasitic in fish, including ecological (Oliva et al ., 2016) and taxonomic studies (molecular and morphological characterization) of some taxa (Oliva et al ., 2014, 2015).…”
Section: Current Research Groups and Their Geographic Distributionmentioning
confidence: 99%
“…The research group from the UA, Chile, has dealt with different subjects concerning helminths parasitic in fish, including ecological (Oliva et al ., 2016) and taxonomic studies (molecular and morphological characterization) of some taxa (Oliva et al ., 2014, 2015).…”
Section: Current Research Groups and Their Geographic Distributionmentioning
confidence: 99%
“…A recent study showed the prevalence of Anisakis spp. in Brama australis in three southern Chilean localities: 16.8% in Lebu, 10.6% in Calbuco and 6.7% in Punta Arenas (Oliva et al, 2016). Several data demonstrate the importance of this nematode parasite in public health and the risk of infection due to this seafood-borne disease worldwide, which affects many different fish species destined for human consumption such as: Chilean jack mackerel (Trachurus murphyi) (George-Nascimento et al, 1983), sardines (Sardina pilchardus) and anchovies (Engraulis encrasicolus) a b c a d (Serracca et al, 2014;Cavallero et al, 2015;Molina-Fernández et al, 2015), Atlantic mackerel (Scomber scombrus) (Pekmezci, 2014), lamprey (Petromyzon marinus) (Bao et al, 2013), golden kingklip (Genypterus blacodes) and snoek (Thyrsites atun) .…”
mentioning
confidence: 94%
“…La reineta es una especie altamente migratoria, caracterizada por un desplazamiento de sur a norte en la temporada de invierno-primavera para desovar, y de norte a sur en la temporada verano-otoño en busca de alimento (Santa Cruz et al, 2014). La dieta de la reineta se compone de un acotado espectro trófico basado en crustáceos de pequeño tamaño (menos de 3 cm) como eufáusidos (Euphausia mucronata), calamares (Loligo gahi) y mictófidos (García y Chong, 2002;Oliva et al, 2016), que forman parte del ciclo biológico de los anisákidos como hospederos intermediarios. Además, la tem-peratura y la salinidad del agua afectan la distribución de estos pequeños crustáceos en la columna de agua (Quesquén y Ayón, 2012).…”
Section: Discussionunclassified